Electrochemical Investigation of Cytochrome c Immobilized onto Self‐Assembled Monolayer of Captopril. Issue 7 (29th May 2013) - Alizadeh, Vali; Mehrgardi, Masoud A.; Fazlollah Mousavi, Mir
Abstract The electrochemical behavior of cytochrome c (cyt‐c) that was electrostatically immobilized onto a self‐assembled monolayer (SAM) of captopril (capt) on a gold electrode has been investigated. Cyclic voltammetry, scanning electrochemical microscopy (SECM) and electrochemical impedance spectroscopy were employed to evaluate the blocking property of the capt SAM. SECM was used to measure the bimolecular electron transfer (ET) kinetics (kBI) between a solution‐based redox probe and the immobilized protein. In addition, the tunneling ET between the immobilized protein and the underlying gold electrode was calculated. A kBI value of (5.0±0.6)×108 mol−1 cm3 s−1 for the bimolecular ET and a standard tunneling rate constant (k0) of 46.4±0.2 s−1 for the tunneling ET have been obtained.